Within-session changes in key and lever pressing for water during several multiple variable-interval schedules - McSweeney, Frances K. (1995)
Rats pressed keys or levers for water reinforcers delivered by several multiple variable-interval schedules. The programmed rate of reinforcement varied from 15 to 240 reinforcers per hour in different conditions. Responding usually increased and then decreased within experimental sessions. As for food reinforcers, the within-session changes in both lever and key pressing were smaller, peaked later, and were more symmetrical around the middle of the session for lower than for higher rates of reinforcement. When schedules provided high rates of reinforcement, some quantitative differences appeared in the within-session changes for lever and key pressing and for food and water. These results imply that basically similar factors produce within-session changes in responding for lever and key pressing and for food and water. The nature of the reinforcer and the choice of response can also influence the quantitative properties of within-session changes at high rates of reinforcement. Finally, the results show that the application of Herrnstein's (1970) equation to rates of responding averaged over the session requires careful consideration.